Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4049/jimmunol.1002029
|View full text |Cite
|
Sign up to set email alerts
|

TRIF Is a Critical Survival Factor in Viral Cardiomyopathy

Abstract: TRIF is a member of the innate immune system known to be involved in viral recognition and type I IFN activation. Because IFNs are thought to play an important role in viral myocarditis, we investigated the role of TRIF in induced myocarditis in mice. Whereas C57BL/6 (wild-type) mice showed only mild myocarditis, including normal survival postinfection with coxsackievirus group B serotype 3 (CVB3), infection of TRIF−/− mice led to the induction of cardiac remodeling, severe heart failure, and 100% mortality (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 44 publications
4
80
1
Order By: Relevance
“…The concordant results demonstrated that CiTRIF can inhibit the replication of GCRV in vitro. TRIF(À/À) mice infected with coxsackievirus group B serotype 3 (CVB3) lead to severe heart failure and 100% mortality (Riad et al, 2011). TRIF overexpression mice are less susceptible to encephalomyocarditis virus (EMCV) infection, have a significantly lower viral load in the heart .…”
Section: Discussionmentioning
confidence: 99%
“…The concordant results demonstrated that CiTRIF can inhibit the replication of GCRV in vitro. TRIF(À/À) mice infected with coxsackievirus group B serotype 3 (CVB3) lead to severe heart failure and 100% mortality (Riad et al, 2011). TRIF overexpression mice are less susceptible to encephalomyocarditis virus (EMCV) infection, have a significantly lower viral load in the heart .…”
Section: Discussionmentioning
confidence: 99%
“…47 Mouse studies have shown that a deficiency of either TLR3 or its adaptor, TRIF, is associated with an increase in levels of virus and mortality after CVB3 or CVB4 infection. [48][49][50] Interestingly, type I IFNs (IFN-a and IFN-b), but not type II IFN (IFN-g), are required for the innate immune response to CVB3. 51 IFN-a and IFN-b are expressed at low levels by various cells but are induced in virally infected cells, such as CFs and cardiomyocytes in the heart.…”
Section: Par1 Modulation Of Tlr3 and Tlr4 Signaling In Cfsmentioning
confidence: 99%
“…For example, in the experimental setting of viral myocarditis, this disease is strongly associated with increased cardiac content of collagens. 21,22 This is also the case in experimental ischemic cardiomyopathy. 23 In nonischemic cardiomyopathy, midwall myocardial fibrosis has been shown to be a major component of pathological remodeling, and to be a predictor of adverse outcome.…”
Section: Stiffness Of Cfbs Derived From Rv and LV Tissue Samplesmentioning
confidence: 99%